Epidemiology of viral hepatitis in the Mediterranean basin - (:unkn) unknown (My University, 2003)
The prevalence of viral hepatitis is high and remains a serious public health challenge throughout the world. New molecular biology techniques provided a better understanding of the viruses over the last decades. Novel therapeutic options seem to be promising but preventing measures including donor screening, immunization against hepatitis A virus (HAV) and hepatitis B virus (HBV), universal use of disposable syringes and implementation of better hygienic conditions play a major role in the control of viral hepatitis. The Mediterranean basin has special demographic and socioeconomic features. We reviewed in this article the seroepidemiological features of viral hepatitis in this particular region. Improving general conditions led to a tendency to be infected in older ages with HAV. Hepatitis B and C virus still remain to be the major causes of chronic hepatitis. The seroprevalence of hepatitis D virus, which was once endemic in the Mediterranean region seem to decrease nowadays whereas hepatitis E virus is still prevalent in some areas. Other viruses such as hepatitis G virus (HGV), TT virus (TTV) and SEN virus do not seem to be a major problem and their clinical importance remains to be determined in further studies.
Keywords: Humans; Hepatitis, Viral, Human; Mediterranean Region; Seroepidemiologic Studies; Socioeconomic Factors